Od totemów do etykiet internetowych. Antropologia i etnografia jako narzędzia badania architektury informacji - Statkiewicz, Robert (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2019)
The main aim of article is depict of anthropological theories and tools, that might be useful for information architecture researchers. AI will be treated as a mental structure representation and compared to the other material structures and systems. Examples from fieldworks and author’s practice display anthropological theories. To sum up, practice of participant design will be presented.